EXPLORING ACTOR ETHICS: NAVIGATING THE INTERSECTION OF MORALITY AND PERFORMANCE (World Bulletin of Social Sciences, 2025)
This scientific article delves into the realm of actor ethics, a multifaceted domain that involves the ethical considerations and responsibilities of individuals engaged in the performing arts. The art of acting has long been a powerful medium for storytelling, cultural expression, and emotional connection. However, the ethical dimensions of acting are complex, involving a delicate balance between artistic freedom and the responsibility to portray characters in a manner that aligns with societal values and moral standards. This article aims to dissect the various facets of actor ethics, examining the challenges, controversies, and evolving perspectives in this dynamic field.
Keywords: Actor Ethics; Authenticity; Stereotypes; Cultural Sensitivity